PENGARUH PERBEDAAN BANTUK BAHAN BAKU DAN SUHU GASIFIKASI AMPAS TEBU TERHADAP PRODUKSI HIDROGEN - Shafwan Amrullah; Theresia Evila Purwanti Sri Rahayu (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2019)
The use of fossil fuel at this time is very disturbing survival, especially related to environmental and economic impacts. While the needs of world anergy continue to increase. The increase reached 80% until 2040. To overcome this problem, scientists have developed gasification technology that can produce fuel as a substitute for fossil fuel. Gasification from biomass can produce synthetic gas that is more environmentally friendly and renewable. so the purpose of this study was to determine the effect of different forms of raw material and temperature on hydrogen produced by the gasification process made from sugarcane bagasse. This research was conducted through a process of gasification made from bagasse biomass to produce synthetic gas that can replace fossil fuel. The type of reactor used is downdraft type reactor. This research was carried out by the gasification process using raw material in the form of sugarcane bagasse with diameters and lengths of 6 mm and 50 mm respectively and the others in the form of fibers. Gasification is also carried out with variations in temperature, namely 800, 950 and 1,050oC. After that, the synthetic gas produced is tested by Gas Chromatography on each variable so that the hydrogen content is known. The hydrogen produced is defined in the form of H2, CH4 products, and the value of hydrogen conversion efficiency. The results obtained showed an increase in H2, CH4, and hydrogen conversion efficiency with an increase in gasification temperature, both in the form of pellets and ash. As for the change in the form of raw materials from pellets to fibers, it causes a decrease in H2, CH4, and hydrogen conversion efficiency values. H2 compositions produced at temperatures of 800, 950, and 1050oC were 10.618, 12.080, 11.312% by volume and 3.025, 2.925, 3.150% by volume, respectively. CH4 composition for raw materials in the form of pellets and fibers at temperatures of 800, 950, and 1050oC were 1.040, 2.622, 2.867% by volume and 0.846, 0.856, 1.051% by volume, respectively. The value obtained is relatively very small compared to the results obtained in previous studies. The value of hydrogen conversion efficiency for raw materials in the form of pellets and fibers at 800, 950, and 1050oC are 1.62%, 3.45%, 3.91% and 1.89%, 1.92%, 2, 32%.